2018
DOI: 10.1021/acsnano.8b05006
|View full text |Cite
|
Sign up to set email alerts
|

Moiré Phonons in Twisted Bilayer MoS2

Abstract: The material choice, layer thickness, and twist angle widely enrich the family of van der Waals heterostructures (vdWHs), providing multiple degrees of freedom to engineer their optical and electronic properties. The moiré patterns in vdWHs create a periodic potential for electrons and excitons to yield many interesting phenomena, such as Hofstadter butterfly spectrum and moiré excitons. Here, in the as-grown/transferred twisted bilayer MoS (tBLMs), one of the simplest prototypes of vdWHs, we show that the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
195
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(224 citation statements)
references
References 79 publications
19
195
0
Order By: Relevance
“…As evidenced in Figure 1e, the maximum lateral size of as‐synthesized Sb 2 Se 3 crystals can reach up to ≈24 µm. It is particularly noteworthy that the growth of second layer is observed on top of the first layer, revealing a typical layered growth mode as demonstrated for other 2D materials, such as MoS 2 , MoSe 2 , WS 2 , WSe 2 42–47. The previous reports have revealed that the reduced surface mobility on the top of the flakes may play roles in the layered growth mode 42,43.…”
Section: Resultsmentioning
confidence: 53%
“…As evidenced in Figure 1e, the maximum lateral size of as‐synthesized Sb 2 Se 3 crystals can reach up to ≈24 µm. It is particularly noteworthy that the growth of second layer is observed on top of the first layer, revealing a typical layered growth mode as demonstrated for other 2D materials, such as MoS 2 , MoSe 2 , WS 2 , WSe 2 42–47. The previous reports have revealed that the reduced surface mobility on the top of the flakes may play roles in the layered growth mode 42,43.…”
Section: Resultsmentioning
confidence: 53%
“…4a). This Raman mode can be assigned as Moiré phonon related with the A 1g phonon branch (here we denote it as FA 1g ), which stems from the offcenter phonons of monolayer linked with the lattice vectors of Moiré reciprocal space 42 . FA 1g peaks exhibit a sine-like behavior with twist angle (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, an exciton in state (ζ′, ν′) scatters to a virtual state within the light cone (Q ≈ 0) via emission or absorption of a phonon and subsequently emits a photon with the remaining energy. The exciton-phonon scattering strength is determined by the effective matrix D, [48][49][50] which is integrated over all possible moiré Umklapp processes, 51 cf. the ESI.…”
Section: Photoluminescence Spectramentioning
confidence: 99%